h y Mira Conci. - Conci, Mira.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2020)
This doctoral dissertation presents a model to evaluate trade-offs between the energetic, economic, and environmental lifecycle performance of building projects. The model is explained so as to be replicable. The model is then applied for decision-making on different strategies for existing buildings in Germany. Results from the case-study show that current state-of-the-art building strategies considerably increase the risk of missing climate change mitigation targets in exchange to a relatively small economic improvement over innovative building strategies.
Glossaries -- Introduction -- Relevance and Background -- Case Study -- Energetic, Economic and Ecological Lifecycle Performance Evaluation Model -- Results -- Summary and Outlook.
Keywords: Construction industry$1 (BManagement.s; Buildings$1 (BDesign and construction.s; Facility management; Construction Management; Building Construction and Design; Facility Management